PERAN BPOM DALAM PEREDARAN PRODUK KOSMETIK ILEGAL DI KECAMATAN KADIA KOTA KENDARI - Waode Purnama Megah Sari; La Ode Muhammad Iman Abdi Anantomo Uke (QAIMUDDIN: Journal of Constitutional Law Review, 2022)
ABSTRACTIllegal cosmetic products are products that contain chemicals and dyes which are prohibited in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 455 of 1998 concerning ingredients, dyes, preservatives and sunscreen in cosmetics. The purpose of this study was to determine the factors causing the circulation of illegal cosmetic products in the Kadia District of Kendari City, to find out the efforts of illegal cosmetic products in the Kadia District of Kendari City and how the legal protection for the community against the circulation of illegal cosmetic products by BPOM in the Kadia District of Kendari City. The type of this research is qualitative with empirical normative research method with the approach of laws and regulations. The collection technique uses observation, interview and documentation techniques.Based on the results of the research that the author did, it can be concluded that: The factors that cause the circulation of illegal cosmetic products in the Kadia District, Kendari City are: Cosmetics originating from abroad that enter illegally, the high market demand factor, the factor affected by misleading advertising, the public ignorance factor the original distribution permit and fake distribution permit, the price of cosmetics registered by BPOM is relatively more expensive, and there is a lack of supervisory staff. BPOM's effort to prevent illegal cosmetic products from circulating in Kadia District, Kendari City is to follow up on illegal cosmetic findings in accordance with their respective violations, including product withdrawal and destruction and court proceedings for criminal acts for those who violate the provisions. Legal protection for the public against the circulation of illegal cosmetic products by BPOM in Kadia District, Kendari City, namely: Always take IEC (communication and education) actions to the community, always carry out routine supervision of shops selling cosmetic products, what kind of cosmetic products are they? sold whether it has obtained the original distribution permit from the BPOM or not.Keywords: BPOM, Illegal Cosmetic Products, Consumer Protection.